Near-infrared-dye labeled tumor vascular-targeted dimer GEBP11 peptide for image-guided surgery in gastric cancer - Tian, Zuhong; Liang, Shuhui; Zhou, Xinmin; Luo, Hui; Tian, Miaomiao; Zhang, Xianghan; Guo, Changcun; Zhang, Jing (Frontiers in Oncology, 2022)
Positive resection margins occur in about 2.8%-8.2% gastric cancer surgery and is associated with poor prognosis. Intraoperative guidance using Near-infrared (NIR) fluorescence imaging is a promising technique for tumor detection and margin assessment. A tumor vascular homing peptide specific for gastric cancer, GEBP11, was developed in our previous work. The goal of this study is to evaluate the efficacy of GEBP11 probes for real-time intraoperative NIR fluorescence imaging guidance. Single and dimeric GEBP11 peptides were synthesized and conjugated with NIR fluorophore dye, Cy5.5. In vitro assay suggested that the GEBP11 NIR probes could bind specifically to tumor vascular epithelial cells, with dimeric peptides showed better affinity. Subcutaneous and orthotopic gastric cancer xenograft mouse models were used to assess the specificity of the GEBP11 NIR probes in vivo. In subcutaneous tumor xenograft mice, live imaging suggested that comparing with free cy5.5 probe, significantly stronger NIR signals could be detected at the tumor site at 24-48h after injection of mono or dimeric GEBP11 probes. Dimeric GEBP11 probe showed prolonged and stronger NIR signals than mono GEBP11 probe. Biodistribution assay suggested that GEBP11 NIR probes were enriched in gastric cancer xenografts. Using dimeric GEBP11 NIR probes in real-time surgery, the tumor margins and peritoneal metastases could be clearly visualized. Complete resection of gastric cancer was confirmed in the surgical specimens. In conclusion, (GEBP11)2-ACP-Cy5.5 could be a potential useful probe for intraoperative florescence guidance in gastric cancer surgery.